1999
DOI: 10.1088/0029-5515/39/11y/303
|View full text |Cite
|
Sign up to set email alerts
|

Overview of radiative improved mode results on TEXTOR-94

Abstract: The radiative improved (RI) mode is a tokamak regime offering many attractive reactor features. In the article, the RI mode of TEXTOR-94 is shown to follow the same scaling as the linear ohmic confinement regime and is thus identified as one of the most fundamental tokamak operational regimes. The current understanding derived from experiments and modelling of the conditions necessary for sustaining the mode is reviewed, as are the mechanisms leading to L-RI mode transition. The article discusses the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 32 publications
2
71
1
Order By: Relevance
“…This regime has been demonstrated for quasistationary periods of several seconds, equivalent to more than 160 energy confinement times or several skin times. 4 In fact, it is very similar to the Z mode 5,6 of ISX-B ͑Impurity Study Experiment B͒ which was, however, observed in a narrower parameter range.…”
mentioning
confidence: 58%
“…This regime has been demonstrated for quasistationary periods of several seconds, equivalent to more than 160 energy confinement times or several skin times. 4 In fact, it is very similar to the Z mode 5,6 of ISX-B ͑Impurity Study Experiment B͒ which was, however, observed in a narrower parameter range.…”
mentioning
confidence: 58%
“…A subject of intense investigations in present day fusion research is the development of an operational scenario, providing at the same time (i) confinement with at least H-mode quality and (ii) high densities around or above the empirical Greenwald density value n GW I P ͞pa 2 [1] [with I P the plasma current (MA), the minor plasma radius (m), and n GW in units 10 20 m 23 ]. Success in this direction has been obtained in the past years on limiter [2,3] and divertor tokamaks by pellet injection or adjusting deuterium fueling and pumping [4,5]. Recently, high energy confinement at a Greenwald numbern e,0 ͞n GW 1.4 (n e,0 being the central averaged chord density) was obtained at DIII-D by optimizing divertor pumping in gas puffed H-mode discharges with edge localized modes (ELM) [6,7].…”
mentioning
confidence: 99%
“…2, where the normalized confinement time t E P 2͞3 tot ͞I P (P tot is the total heating power in MW) is plotted versus the Greenwald numbern e,0 ͞n GW as introduced in Ref. [3]. The data in this diagram, which have been obtained after a fresh siliconization, illustrate three types of behavior depending on the deuterium (D) gas fueling rate.…”
mentioning
confidence: 99%
“…This new operational regime was discovered in the Impurity Study Experiment ͑ISX-B͒ tokamak 5 and then confirmed and thoroughly reinvestigated on the Tokamak Experiment for Technology Oriented Research ͑TEXTOR-94͒. 6,7 Compared to the L ͑low͒ confinement mode, the RI mode is characterized by more peaked density and temperature profiles, larger operating densities ͑N e may be well above the Greenwald limit͒, and larger confinement times ͓ E may be close to edge localized mode ͑ELM͒ H-mode values͔. The mechanisms considered presently to lead to confinement improvement in the RI mode are largely based on the reduction of the growth rate of the toroidal ion temperature gradient ͑ITG͒ mode when the plasma Z eff increases.…”
Section: Introductionmentioning
confidence: 75%
“…[6][7][8] We may thus conclude that flow generation due to radiation asymmetry effects may not be important for hot edge plasmas. We now present a semiquantitative explanation of how a small poloidal asymmetry in the radiated power can modify the basic characteristic of L-mode discharges and then lead to a L-RI mode transition.…”
Section: Applications Of the Theorymentioning
confidence: 99%